Flying qualities and flight control system design for a fly-by-wire transport aircraft - Gautrey, Jim (Cranfield University, 1998)
Fly-by-wire flight control systems are becoming more common in both civil and military aircraft. These systems give many benefits, but also present a new set of problems due to their increased complexity compared to conventional systems and the larger choice of options that they provide. The work presented here considers the application of fly-by-wire to a generic regional transport aircraft. The flying qualities criteria used for typical flying qualities evaluations are described briefly followed by analysis of several past transport aircraft flying qualities programmes against these criteria. From these results, some control law independent design requirements are formulated for a civil aircraft for the approach and landing task. These control law independent flying qualities criteria are intended to be used with any generic rate-like control law for a transport aircraft and enabled a number of different control laws to be designed. The results of a number of flying qualities evaluations are presented. Both an ILS approach task and a formation flying task were used. The effects of windshear were also considered. It was found that control laws which maintain flight path are suitable for the ILS approach task, while most rate-like response characteristics give good flying qualities for the formation flying task. Finally, the conclusions drawn from these evaluations are presented, and both the Civil and Military current airworthiness requirements are assessed. In addition to the flying qualities work, a study is made of the management issues associated with fly-by-wire design. A fly-by-wire aircraft design programme was proposed and the project management issues associated with this were considered. A timescale was proposed for the design process for a generic regional aircraft, and the critical path for this process is presented.
Keywords: fly-by-wire